ANALISIS SWOT SEBAGAI DASAR KEPUTUSAN STRATEGI PEMASARAN PADA PERUSAHAAN SERVER PULSA DI KOTA BATAM (STUDI KASUS PADA CV. STAR PRATAMA) - Rahmat Hidayat; Ricky Rahmat (Politeknik Negeri Batam, 2018)
This study aims to determine the factors that become the strengths and weaknesses, the factors that become challenges and threats, knowing how the position of CV STAR PRATAMA server business compared with other server business and strategy that must be applied by the CV STAR PRATAMA server business. From the results of the study using SWOT analysis shows that based on the SWOT diagram, CV STAR PRATAMA has a position in quadrant I. In this quadrant is very profitable, based on the Matrix IE (Internal-External Matrix) then CV STAR PRATAMA is on the cell and analysis results In the final stage of using QSPM, it can be seen that the current strategy is one of the ST (Strength-Threat) strategy that is by improving the excellent service and after sales service to satisfy the customer.